Urgensi Kode Etik Profesi Advokat dalam Menjaga Eksistensi Sebagai Profesi Terhormat - Riana Wijiana (Pusat Riset dan Inovasi Nasional, 2025)
The code of ethics of the advocate profession plays an important role in maintaining the existence of this profession as a respected officium nobile. As part of the justice system, advocates are not only required to have legal expertise, but also to maintain integrity and morality through compliance with the code of ethics. This article discusses the urgency of implementing the code of ethics of the advocate profession, its strategic function in regulating relations with clients, courts, and the community, and the challenges it faces. Enforcement of the code of ethics is carried out through supervision of professional organizations and the Honorary Council to prevent violations that can tarnish the reputation of the profession. Factors such as legal ethics education for prospective advocates, harmonization of codes of ethics between organizations, and sanction mechanisms are the main concerns in strengthening its implementation. In addition, the digital era brings new challenges in the form of public perception of the advocate profession influenced by social media. This article highlights the importance of collaboration between educational institutions, professional organizations, and advocates in building an ethical culture and increasing public trust. Enforcement of the code of ethics not only maintains the honor of individual advocates, but also protects public trust in the legal system as a whole.